THE MASS MEDIA ROLE IN DISSEMINATING AGRICULTURAL INFORMATION TO VEGETABLE FARMERS IN LAMPUNG - Sumaryo Sumaryo (Jurnal Penyuluhan, 2006)
The objective of this study was to describe the role of mass media, especially television in disseminating agricultural information to vegetable farmers in sub-urban and rural areas. The sample of the study was 55 farmers, who were randomly selected from a 550 farmer population. The findings pointed out that farmers in general were not interested in the broadcasted agricultural programs, since the programs’ contents did not match their needs. Additionally, the farmers in the city of Bandar Lampung watched a lot more varieties of television programs than those resided in the West Lampung district.